Analysis of Sciences Process Skills of Science Education Students in Microbiology Practice - Sari, Mella Mutika; Yulinda, Ratna; Zubaidah, Siti (Asian Journal of Science Education, 2023)
This study aims to assess the science process skills level of Science Education Study Program Teacher Training and Education Faculty Lambung Mangkurat University (FKIP ULM) students in the 2020/2021 academic year. This research employed a qualitative research. Data collection was conducted using validated scientific process skills observation sheets. Observations were made on 27 students of the Science Education Program FKIP ULM who conducted SPS-based practicum activities The data obtained was analyzed descriptively qualitatively using percentages on the eight items in the SPS section, namely skills, formulating problem formulation, identifying variables, defining operationally, developing hypotheses, making observations, designing experiments, analyzing data/information, and making conclusions. The results showed that student SPS is categorized very well on basic SPS and sufficient category on integrated SPS (defining variables operationally, designing experiments, and analyzing data/information). It directs learning to improve on integrated SPS so that in the end students can master the integrated SPS well.